Competency Analysis in the Implementation of the Projek Penguatan Profil Pelajar Pancasila on the Local Wisdom Theme - Sufyadi, Susanti; Sadila, Adinda; Utama, Agus Hadi; Qomario, Qomario; Afriandy, M (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
The development of local wisdom in a region is influenced by one of the natural characteristics of the region which requires the community to adapt in order to live well in the region, local wisdom is one of the themes in the Projek Penguatan Profil Pelajar Pancasila because it is related to various sectors and is a reference and applied in daily community activities. The wetland area of South Kalimantan has several local wisdoms including Kayuh baimbai (cooperation), Gawi sabumi (mutual cooperation), Basusun Sirih (integrity), and Menyisir sisi tapih (introspection). The purpose of this study was to analyze the competency needs of teachers at Junior High School 7 Banjarmasin which will be a reference for developing a model for increasing teacher capacity in implementing the Projek Penguatan Profil Pelajar Pancasila on the theme of Local Wisdom. It was carried out in two stages, namely training needs analysis using the TNA model and developing a conceptual model using the Smith and Ragan model. The study identified 10 teacher competency needs, so that the conceptual model developed in the form of workshops and ongoing mentoring, was designed with learning objectives referring to the 10 competencies. The results of the study concluded that competency needs analysis activities can be equated or carried out with evaluation activities, the implementation of the analysis also showed an impact on changes in the mindset of teachers who were the targets of the study, needs analysis activities provided information to teachers that were considered by teachers.